THE IMPACT OF A SINGLE AND CONTINUOUS AUDIOVISUAL STIMULATION ON HEART RATE VARIABILITY AND MECHANISMS OF AUTONOMIC REGULATION IN ATHLETES-CYCLICS - R. I. Aizman; M. S. Golovin (Бюллетень сибирской медицины)
The purpose of this study was to investigate the effect of influence of single and prolonged exposure of audio-visual stimulation (AVS) on heart rate variability and the mechanisms of the autonomic regulation in athletes, involved in cyclic sports activity.Material and methods. In this study 60 athletes aging of 17–23 years old, specializing in middle-distance running, were involved. The running volume in the zones of varying intensity was from 185 to 225 km/month. The experiment was conducted in January – March 2014, at the Scientific Educational Center “Physiology of ontogenesis” at the Department of Anatomy, Physiology and Life Safety of NSPU.Training course of audiovisual stimulation (AVS) consisted of 20–22 sessions, which were conducted in a day with using a portable audiovisual stimulator “NOVO PRO” (USA). ECG registration signal was performed using hardware and software complex VNS-Micro (Neurosoft, Ivanovo, Russia) in standard electrocardiogram lead II. Athletes who received AVS course in the morning, before sports training loads, have received training with activating program, and after exercise – by using a relaxed program.Results. In athletes after 20–22 sessions of AVS the decreased influence of the sympathetic regulation and contribution of central levels of management in the regulation of heart rate were found. A decrease of intensity of regulatory system was observed.Increased influence of the parasympathetic regulation and strengthening of autonomous regulation contour was found. AVS contributed to increasing influence of respiratory waves on the heart rhythm and a more economical functional activity. AVS single exposure caused a significant increase in the functioning of autonomous regulation contour, the growing influence of parasympathetic effects and higher contribution of respiratory waves in the formation of heart rate by using activating as well relaxing programs. However, a more pronounced effect was observed after application of relaxing program.Conclusion. Application of AVS contributed to increase activity of the parasympathetic nervous system, the growing influence of autonomous regulation contour, the increase influence of respiratory waves on the heart rhythm and a more economical its work at rest and during an orthostatic test. AVS training may be recommended by sports training for maintaining top competition form, faster recovery and improve the functional state of regulation mechanisms.